Proliferation of macrophages due to the inhibition of inducible nitric oxide synthesis by oxidized low-density lipoproteins - Brunner, Monika; Gruber, Miriam; Schmid, Diethart; Baran, Halina; Moeslinger, Thomas (Technische Universität Dortmund, 2015)
Oxidized low-density lipoprotein (ox–LDL) is assumed to be a major causal agent in hypercholesteraemia-induced atherosclerosis. Because the proliferation of lipid-loaden macrophages within atherosclerotic lesions has been described, we investigated the dependence of macrophage proliferation on the inhibition of inducible nitric oxide synthase (iNOS) by hypochlorite oxidized LDL. Ox–LDL induces a dose dependent inhibition of inducible nitric oxide synthesis in lipopolysaccharide-interferon stimulated mouse macrophages (J774.A1) with concomitant macrophage proliferation as assayed by cell counting, tritiated-thymidine incorporation and measurement of cell protein. Native LDL did not influence macrophage proliferation and inducible nitric oxide synthesis. iNOS protein and mRNA was reduced by HOCl-oxidized LDL (0–40 µg/ml) as revealed by immunoblotting and competitive semiquantitative PCR. Macrophage proliferation was increased by the addition of the iNOS inhibitor L–NAME. The addition of ox–LDL to L–NAME containing incubations induced no further statistically significant increase in cell number. Nitric oxide donors decreased ox–LDL induced macrophage proliferation and nitric oxide scavengers restored macrophage proliferation to the initial values achieved by ox–LDL. The decrease of cytosolic DNA fragments in stimulated macrophages incubated with ox-LDL demonstrates that the proliferative actions of ox-LDL are associated with a decrease of NO-induced apoptosis. Our data show that inhibition of iNOS dependent nitric oxide production caused by hypochlorite oxidized LDL enhances macrophage proliferation. This might be a key event in the pathogenesis of atherosclerotic lesions.
EXCLI Journal ; Vol. 14, 2015
Keywords: inducible nitric oxide synthase; lipoproteins; macrophages; atherosclerosis; 610